Proteomic Analysis of Wheat Seed in Response to Drought Stress - Yu-feng ZHANG; Xiu-wen HUANG; Li-li WANG; Liu WEI; Zhi-hui WU; Ming-shan YOU; Bao-yun LI (Journal of Integrative Agriculture, 2014)
Drought stress is one of the major factors affecting in wheat yield and grain quality. In order to investigate how drought stress might influence wheat quality during grain filling, three wheat cultivars Gaocheng 8901, Jagger and Nongda 3406 were subjected to drought stress during the grain filling stage. Neither globulin and glutenin, nor the relative percentage of amylose significantly changed following drought treatments, whereas albumin and gliadin concentrations did. The SDS-sedimentation, which has a strong linear correlation with wheat baking quality was markedly decreased following drought stress. These results indicated that drought had an adverse effect on wheat quality. In order to investigate the protein complexes in the wheat flour, the data from native PAGE and SDS-PAGE were combined and a total of 14 spots were successfully identified, and of these eight protein types were determined to be potential complex forming proteins.